2022
DOI: 10.3390/brainsci12101328
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting the Possibility of Peripheral Neuropathy in Patients with Type 2 Diabetes Mellitus

Abstract: Background and Purpose: Diabetic peripheral neuropathy (DPN) leads to ulceration, noninvasive amputation, and long-term disability. This study aimed to develop and validate a nomogram for forecasting the probability of DPN in type 2 diabetes mellitus patients. Methods: From February 2017 to May 2021, 778 patients with type 2 diabetes mellitus were included in this study. We confirmed the diagnosis of DPN according to the Toronto Expert Consensus. Patients were randomly divided into a training cohort (n = 519) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…At the sama time, the area under the curve (AUC) of the column chart model designed by Wanli Zhang et al. was 0.763 in the training queue and 0.755 in the validation queue ( 11 ). Jing Yang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the sama time, the area under the curve (AUC) of the column chart model designed by Wanli Zhang et al. was 0.763 in the training queue and 0.755 in the validation queue ( 11 ). Jing Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration curve further confirmed the model's precision in estimating the risk of DPN. At the sama time, the area under the curve (AUC) of the column chart model designed by Wanli Zhang et al was 0.763 in the training queue and 0.755 in the validation queue (11). Jing Yang et al found serum creatinine (Scr), hypertension, glycosylated hemoglobin A1c (HbA1c), blood urea nitrogen (BUN), body mass index (BMI), triglycerides (TG), and diabetic peripheral neuropathy (DPN) Can serve as a key factor for this prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…DPN has long been considered “progressive and irreversible”. It is mainly manifested as pain, numbness, and paresthesia in the glove-sock-like distribution area at the end of the extremities, seriously influencing the patients’ quality of life, and results in a heavy social burden [ 5 , 6 , 7 ]. In recent years, it has generally been demonstrated to be the result of a combination of factors including long-term hyperglycemia caused by metabolic disorders, microcirculation disorders, and neuroischemia, and hypoxia [ 8 ].…”
Section: Introductionmentioning
confidence: 99%